Host–guest interaction-based supramolecular prodrug self-assemblies for GSH-consumption augmented chemotherapy. Issue 26 (20th June 2022) - Bai, Yang; Li, Xihua; Li, Muqiong; Shang, Qingqing; Yang, Jing; Fan, Li; Tian, Wei
Abstract : The chemotherapy is perplexed by the unsatisfied efficacy due to the GSH-induced detoxification. The SPSAs reported in this study could not only consume GSH but also reduce GSH biosynthesis pathway, paving a novel way to enhance therapeutic efficacy. Abstract : The over-expressed cellular glutathione (GSH) severely restricts the chemotherapeutic efficacy due to the GSH-induced detoxification of chemical drugs. Herein, how to construct effective drug delivery systems with GSH-consumption property is still a general concern and a major challenge. In this study, the host–guest interactions between water-soluble pillar[6]arene (WP[6]) and chlorambucil-arylboronic acid (Cb-BA) were utilized to construct supramolecular prodrug self-assemblies (SPSAs) with specific stimuli-responsive property. Notably, the BA moiety could not only consume GSH but also rapidly bind curcumin (Cur), which could inhibit the thioredoxin reductase (TrxR) to further reduce the GSH biosynthesis pathway. Benefiting from the functionality of BA-Cur conjugates, the GSH levels could be significantly downregulated, paving a novel way to enhance chemotherapeutic efficacy. In vitro and in vivo investigations demonstrated that this two-pronged GSH-depletion strategy could amplify the cellular oxidative stress and achieve excellent anti-tumor efficacy.